CAMPUR KODE PENGGUNAAN BAHASA INDONESIA OLEH MAHASISWA THAILAND DI UNIVERSITAS JEMBER - Nurul Azizah; A. Erna Rochiyati S.; Edy Hariyadi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2019)
Code mixing is a state of language use by speakers by mixing two (or more) languages in one speech without any cause for the mixture of languages. One of these codes mixes in the communication process of Thai University students at Jember when using Indonesian. Code interfering events occur when used as communication tools and adaptation tools, interact daily and in the learning process. This study uses a qualitative descriptive method using a sociolinguistic approach. The data in this study are Thai student speeches when using Indonesian. The results showed that mixed code was found when Thai students used Indonesian. From the results of the study found three mixed codes: 1) mixed word code, 2) mixed code form phrases, and mixed code form clauses. The code interfering factors include: 1) regional sense factors, 2) financial factors to explain and interpret, 3) factors in the absence of concepts or terms in Indonesian, and 4) factors of limitations in mastering Indonesian.